SUSTAINABILITY AND QUALITY COSTS IN THE HIGHER EDUCATION INSTITUTIONS - Velkoska, Cvetanka (International Scientific Journal Vision, 2024)
This paper explores the quality cost models in higher education institutions, that can help in the function of planning the cost of quality in higher education, monitoring and analyzing the cost of quality to locate the weak points in the operation and reduce and prevent unproductive spending from the aspect of quality. Sustainable development as a concept should be integrated into quality cost management not only in manufacturing but also in service activities such as higher education. This study focuses on quality costs within the framework of sustainability in higher education institutions. The research methodology involves a logical, systematic analysis of scientific research, situational analysis using comparative and summary methods. In this study is proposed a quality cost model for identifying quality cost elements with examples of quality cost elements. Incorporating the three dimensions of sustainability (economic, ecological, and social) into quality cost model involves considering the broader impacts and benefits of quality costs beyond just quality improvement. The paper advocates for incorporating preventive measures and sustainable practices to reduce failure costs and promote long-term sustainability goals. Future research directions include developing quality cost models that incorporate sustainability concept. The successful implementation of quality costs from the sustainability perspective requires commitment from top management, data-driven decisionmaking, and stakeholder engagement, ultimately leading to higher quality standards and sustainable development in higher education